Windows Server 2016: High Availability. - McMillen, Robert (linkedin.com, 2017)
Review high-availability Windows Server features, and prepare for the fifth domain of Exam 70-743 Upgrading Your Skills to MCSA: Windows Server 2016—Implement high availability.